Vitreous substitutes and tamponades – A review of types, applications, and future directions - Manoj P Shettigar; Vivek Pravin Dave; Hung-Da Chou; Adrian Fung; Eleonore Iguban; Francesc March de Ribot; Camille Zabala; Yi-Ting Hsieh; Geeta Lalwani (Indian Journal of Ophthalmology, 2024)
Vitreous substitutes and tamponades occupy the vitreous cavity following vitrectomy in the management of various conditions such as retinal detachment, macular hole, and diabetic retinopathy. Such replacements can be for the short term (gases such as sulfur hexafluoride (SF6) and perfluoropropane (C3F8) or long term (such as silicone oils). Certain substitutes such as perfluorocarbon liquids are used only transiently during surgery as “a third hand” or rarely till a few days post surgery. Hydrogels and hyaluronan derivatives are among the newer vitreous substitutes that are showing promise for the future, albeit still under investigation. still being investigated for use as vitreous substitutes. These materials have properties similar to the natural vitreous and may offer advantages such as improved biocompatibility and biodegradability. Although vitreous substitutes are valuable tools in treating vitreoretinal conditions, they carry risks and potential complications such as cataract formation, glaucoma, and inflammation. The current communication extensively reviews the available literature on vitreous tamponades. It details the composition and properties of various vitreous substitutes and tamponades available for the clinician, highlighting the techniques of usage, indications, and limitations.